Emergency management of avulsion injuries: from home to clinic. A multicentre cross-sectional survey among medical doctors and general public - Alam, Mafaza; Faraid, Varqa; Alam, Laima; Yousaf, Ajmal; Shah, Pir Jawad Ali; Wahid, Maham (Journal of the Pakistan Medical Association, 2022)
The objective of this multi-centre study was to analyse the knowledge of parents as compared to medical-doctors regarding avulsion-injuries. A validated and piloted questionnaire was circulated among two equal groups (130 participants each) of medical-doctors and the general public. Data was analysed using SPSS version 19. A total of 131 (89%) participants had a university degree and 185 (71%) had a full time employment. One hundred and eighty-seven (72%) participants reported having no previous information regarding avulsion injuries, 195 (75%) considered their level of knowledge inadequate, and 63 (24%) had a previous history of dental trauma. A statistically significant number had information regarding avulsed permanent-teeth replantation (p = 0.02) but not deciduous-teeth (p = 0.26), whereas only 39 (15%) were aware of the right medium for tooth storage. Having seen or sustained an avulsion-injury and a higher qualification were statistically related to correct responses for some questions. A total of 106 (41%) of the participants wanted to be educated through written-material. In conclusion, the first-aid knowledge regarding tooth avulsion injuries in our population, irrespective of their level of academic education, is poor and needs supervised training. Keywords: Dental trauma, dental knowledge, dental management, tooth avulsion.